Monetary reward mechanism for promoting online knowledge sharing: A modeling study - Xuhui Hu; Yang Qin; Lu-Xing Yang; Xiaofan Yang (PLoS ONE, 2025)
Knowledge sharing is critical for an organization to acquire sustained competitive advantage. Bestowing monetary rewards may possibly the most direct method of stimulating online knowledge sharing. Under the monetary reward mechanism for promoting knowledge sharing, we intend to find a satisfactory knowledge-sharing promotion policy. First, based on a state evolutionary model for the knowledge-sharing community, we reduce the original problem to an optimal control model. Second, applying optimal control theory to the model, we give an algorithm for solving the model. Next, we validate the feasibility of the algorithm. Finally, we inspect the applicability of the algorithm. To our knowledge, this is the first time the optimal control modeling technique is applied to the research of knowledge sharing.